Prostate cancer testicular metastasis: Are they underestimated? Case report and analysis of the literature. Issue 4 (November 2022) - Smelzo, Salvatore; Mantica, Guglielmo; Lucianò, Roberta; Tenace, Nazario Pio; De Marchi, Davide; Pini, Giovannalberto; Passaretti, Giovanni; Losa, Andrea; Gaboardi, Franco
Introduction: We aim to present a rare case of a patient who developed a late testicular metastasis of PCa after radical prostatectomy. Case description: A 78 years old man presenting for left testicular swelling slowly increasing of size over the last 2 months. He underwent a retropubic radical prostatectomy and extended bilateral lymphadenectomy in 2007 for prostatic adenocarcinoma. At the time of the presentation the last PSA was 0.91 ng/mL. The patient underwent a standard left orchifunicolectomy in April 2019 without intra- or perioperative complications. The pathological analysis showed a testicular metastasis of acinar adenocarcinoma. Conclusions: In conclusion, testicular metastasis from PCa are uncommon conditions. PSA evaluation and physical examination of all sites of metastasis and accurate evaluation of all signs/symptoms during the clinical visit remains crucial to the diagnosis of recurrence.